MEMBANGUN IMUNITAS INFORMASI KELUARGA: PENGUATAN LITERASI UNTUK MENANGGULANGI HOAKS MELALUI PENGGERAK PKK ANDONG - Alhasbi, Faruq; Fathurrahman, Muhammad; Widoyo, Agus Fatuh; Alfauzi, Ikhsanurdien; Java, Abyanuddin Al; Liswara, Musa Ahmad; Fahrurrozi, F; Mufasiroh, Hanif Fika (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This community service aims to enhance the media literacy of Penggerak PKK Andong in identifying and combating hoaxed information. This phenomenon causes information confusion, conflict, and unrest, exacerbated by the lack of understanding and information verification skills in the assisted communities, including Kelurahan Andong. Initial observations showed the high prevalence of hoaxes, indicating the urgency of media literacy activities. Women (mothers) play a vital role in maintaining the quality of information, so equipping them with knowledge and ways to tackle hoaxes is crucial to building strong family information immunity. The agenda implementation method includes interactive socialization and workshops that equip participants with four verification steps (check the source, look for comparative info, examine the content, and take action quickly), followed by continuous post-socialization mentoring to ensure the materials are implemented well, encouraging participants to actively identify and tackle hoaxes in the community, especially families. The results showed a significant increase in the PKK women's understanding of hoaxes, the dangers they pose, and the factors that lead to their spread. In addition, their practical skills in verifying news and taking preventive action also improved. PKK mothers are now more empowered to become anti-hoax agents, contributing to a healthier information environment in Kelurahan Andong Boyolali.